Nematodes Resistance on Anthelmintics Group of Benzimidazole in Ruminants - Yanuartono Yanuartono; Soedarmanto Indarjulianto; Alfarisa Nururrozi; Hary Purnamaningsih (Universitas Tidar, 2019)
One factor that inhibits the increase in ruminant productivity is nematode infection. It’s cause a decrease in feed intake, weight gain, milk production, disease, death, and expensive medical expenses The control of gastrointestinal nematode infections in livestock, over the past decades is primarily based on the preventive or curative use of chemotherapeutics and generally uses broad-spectrum anthelmintic such as benzimidazole, probenzimidazole, imidazothiazole, macrolide and ivermectin. The widespread use of several antelmintic groups now causes an increase in the incidence of gastrointestinal nematodes resistance against anthelmintics. Anthelmintics derived from various types of plants are expected to replace the benzimidazole so that it can reduce the level of resistance of the gastrointestinal nematodes in ruminants. However, for the future there is still a lot of research needed to further improve the ability of natural medicinal drugs to cope with gastrointestinal nematode infections in ruminants. Keywords : benzimidazole, nematode,resistance, ruminants